Computing polynomial functions of correlated sources: Inner bounds - Sheng Huang; Skoglund, M. (2012 International Symposium on Information Theory and Its Applications, 2012)
This paper considers the problem of source coding for computing functions of correlated i.i.d. random sources. The approach of combining standard and linear random coding for this problem was first introduced by Ahlswede and Han, in the special case of computing the modulo-two sum. In this paper, making use of an adapted version of that method, we generalize their result to more sophisticated scenarios, where the functions to be computed are polynomial functions. Since all discrete functions are fundamentally restrictions of polynomial functions, our results are universally applied.